The 14C AMS system at The University of Georgia - Roberts, M. L.; Culp, R. A.; Dvoracek, D. K.; Hodgins, G. W. L.; Neary, M. P.; Noakes, J. E. (Proceedings of the Ninth International Conference on Accelerator Mass Spectrometry, 2004)
The Center for Applied Isotope Studies at the University of Georgia has installed a compact 14C accelerator mass spectrometry (AMS) system manufactured by the National Electrostatics Corporation, Middleton, Wisconsin. The system utilizes a 134 sample ion source and a 500 kV Pelletron. In terms of cost and size, the new system is a significant advance over previous technology. Details and performance of the new system will be presented.
id: 2103